TRANSFORMASI BAHASA INDONESIA DALAM KONTEKS DIGITAL : PERUBAHAN PADA STUKTUR DAN BENTUK BAHASA - Muhammad Arifin Ilham; Rinaldi Supriadi; Mohammad Zaka Al Farisi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to find out how digital technology influences grammar, vocabulary and communication style, especially in the use of abbreviations, emojis and slang in text messages and social media. The method used in this research is a qualitative method with a literature study approach, as well as journals and articles that discuss language and digital technology as sources. The process is preparing appropriate sources, classifying data from these sources, and finally verifying or drawing conclusions from the data that has been collected. At this stage, an analysis is carried out to identify how digital technology influences grammar, vocabulary and communication style, especially in the use of abbreviations, emojis and slang in text messages and social media. The results of this research are that there are several influences of digital technology on changes in structure and form in the Indonesian language.